PENGEMBANGAN KOMPOSIT ZIF-8 DENGAN LOGAM OKSIDA - Sardi, Adelia Maritza; Syaima, Husna (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
This review article discusses the effectiveness of composite synthesis methods for ZIF-8 with metal oxides and their applications in various fields. ZIF-8 is a popular metal-organic framework due to its stability; however, it has limitations, such as low conductivity, limited catalytic activity, and poor recyclability. To address these issues, various methods for synthesizing ZIF-8-metal oxide composites have been developed in recent years. These composites demonstrate significant potential to enhance performance in applications like photocatalysis and energy storage, as metal oxide-based materials can provide higher energy density and improved conductivity. This review presents a recent comparison of different synthesis methods to provide further insights into developing these materials for industrial applications. Keywords : Metal Oxide, ZIF-8, ZIF-8 Composite Synthesis